Deaths related to post-COVID in Italy: a national study based on death certificates - Grippo, Francesco; Minelli, Giada; Crialesi, Roberta; Marchetti, Stefano; Pricci, Flavia; Onder, Graziano (Frontiers in Medicine, 2024)
Introduction SARS-CoV-2 infection has been associated with the onset or persistence of symptoms in the long-term after the acute infection is resolved. This condition known as Post-COVID, might be particularly severe and potentially life-threatening. However, little is known on the impact of post-COVID condition on mortality. Aim of the present study is to assess and quantify Post-COVID deaths in Italy in years 2020 and 2021, based on an analysis of death certificates. Methods Data from the Italian National Cause of Death Register were analyzed. ICD-10 code U09.9, released by the World Health Organization in September 2020, was used to identify the ‘Post-COVID’ condition. Numbers of post-COVID deaths from October 2020 to December 2021 were analyzed. Rates of post-COVID deaths were calculated for the year 2021. Results Between October 2020 and December 2021, 4,752 death certificates reporting post-COVID condition were identified. Of these, 14.9% (n = 706) occurred between October and December 2020 and 85.1% (n = 4,046) in 2021. In 46.0% of post-COVID-related deaths, the underlying cause of death was COVID-19. Other frequent underlying causes were heart disease (14.3% of cases), neoplasms (9.2%), cerebrovascular diseases (6.3%) and Alzheimer’s disease and other dementias (5.5%). The mortality rate related to post-COVID conditions in year 2021 was 5.1 deaths per 100 thousand inhabitants and it increased with increasing age. Men showed a higher mortality rate than women (4.3 deaths per 100 thousand in women and 6.0 deaths per 100 thousand in men). Discussion Post-COVID conditions contributed to a substantial number of deaths in Italy. Strategies to identify the population at risk of severe long-term consequences of SARS-CoV-2 infection and interventions aimed at reducing this risk must be developed.